Assessment of ankle plantar flexor neuromuscular properties: A reliability study. (December 2021) - Tavakkoli Oskouei, Sanam; Malliaras, Peter; D Hill, Keith; Garofolini, Alessandro; Clark, Ross; Perraton, Luke
Abstract: This study aimed to determine test–retest reliability of ankle plantar flexor neuromuscular properties in healthy people to improve understanding of additional measurement and analysis procedures that may be used in outcome assessment. Ten healthy participants (age 29.60 ± 5.36 years) volunteered. Isometric torquemax, rate of torque development (RTD), rate of electromyography rise (RER), impulse, electromechanical delay (EMD), torque steadiness, and torque sensing were obtained during two testing sessions 60 min apart. ICC values ranged from 0.81 to 0.99, indicating good to excellent test–retest reliability. Lower bands of the 95 % CIs were all above 0.75 apart from the early phase measures (≤50  ms ) derived from explosive torque-time and EMG-time curves, which were between 0.32 and 0.73, indicating poor to moderate reliability. Heteroscedasticity was observed for RTD, impulse, and EMD. LOA as a function of the mean (X̅) for these measures ranged from meandifference  ± 0.25X̅ to ± 0.68X̅. EMD showed excellent reliability (ICC = 0.90; 95 % CI [0.63, 0.98]). Torque sensing and torque steadiness showed good reliability (0.81 ≤ ICC ≤ 0.89). Thus, ankle plantar flexor neuromuscular properties showed good to excellent test–retest reliability. However, reliability of measures in the early phase of muscle contraction were consistently lower than the late phase.